Revisiting the Institutional English Proficiency Test (EPT): Evaluating Its Validity, Reliability, and CEFR Alignment - Moh. Syafik; Eva Nikmatul Rabbianty; Yazid Basthomi; Ling Gan; Nurul Hadi (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background: There is an urgency for institutions to develop standardized English proficiency tests for individual use, given the unaffordable and unreachable high-stakes tests for some academic communities. Therefore, the Center for Language Development of IAIN Madura developed EPT (English Proficiency Test) as an individual English test. Nevertheless, no research has provided evidence that EPT has been standardized.Methodology: This quantitative consequential research invited four subject matter experts (SMEs) to judge the objectives of the test items to validate the content validity (CV) with the item-objective congruence (IOC) formula and assess three ways of language proficiency assessment to see how the EPT aligns with the Common European Framework of Reference for Languages (CEFR).Findings: The results revealed that the CV and reliability of EPT had been achieved, with the IOC for the three skills measured above 0.75. Internal consistency and stability were also proven to have high reliability coefficients. However, no evidence indicates alignment between EPT and CEFR, as the administrator was found not to follow the three validation frameworks: what is assessed (specification), how performance is interpreted (standardization), and how comparison is made (standard setting).Conclusion: The results conclude that EPT should be improved by aligning it with CEFR. Administrators should conduct a standard-setting study to map EPT scores onto the CEFR and provide the minimum scores (cut scores) needed to enter each targeted CEFR level.Originality: This research fills the knowledge gap by evaluating the EPT’s alignment with CEFR and addressing the need for a standardized and affordable language test in Indonesia.